Identification of T‐cell epitopes from benzylpenicillin conjugated to human serum albumin and implication in penicillin allergy. Issue 8 (27th February 2018) - Azoury, M. E.; Filì, L.; Bechara, R.; Scornet, N.; de Chaisemartin, L.; Weaver, R. J.; Claude, N.; Maillere, B.; Parronchi, P.; Joseph, D.; Pallardy, M.
Abstract: Background: There is in vitro evidence that T cells from allergic patients react to benzylpenicillin‐human serum albumin (BP‐HSA) bioconjugates. Our group has recently shown the existence of naïve CD4 + T cells recognizing BP‐HSA in healthy donors. However, BP‐haptenated peptides from HSA participating in the immunization of allergic patients have never been identified. The purpose of the present study is to identify immunodominant BP‐haptenated peptides from HSA involved in immunization of patients to BP and to refine the frequency calculation of naïve CD4 + T cells recognizing BP. Methods: Co‐cultures were established with CD4 + T cells from non‐allergic donors and mature autologous dendritic cells (DCs) loaded with BP‐HSA or BP‐haptenated peptides from HSA. The CD4 + T‐cell response specific for BP‐HSA or for individual BP‐haptenated peptides was measured using an interferon‐γ (IFN‐γ) ELISpot assay. The frequency of BP‐specific CD4 + T cells was then calculated using the Poisson distribution. BP‐HSA and BP‐haptenated peptides recognition by allergic patients was evaluated on peripheral blood mononuclear cells (PBMCs) using a lymphocyte transformation test (LTT). Results: Results showed that BP‐HSA and BP‐haptenated peptides were recognized by naïve T cells from 15/16 and 13/14 tested healthy donors, respectively. Most donors responded to 3 peptides with BP covalently bound on lysines 159, 212, and 525. Two of these benzylpenicilloylated peptides (lysines 159 and 525) were also found to induce PBMCs proliferation in patients with allergic reaction to penicillins. Conclusion: This study identifies and characterizes for the first time the BP‐haptenated peptides from HSA involved in the immunization of patients to penicillins.